Distribution of Short-chain Aliphatic Aldehydes in the Gastrointestinal Tract of Pigs (P06-033-19) - Zhou, Yuyin (Curr Dev Nutr, 2019)
OBJECTIVES: The presence of short-chain aliphatic aldehydes (SCAAs), including acetaldehyde, propanal, butanal, and pentanal, in food has been detected. In addition, the production of SCAAs in the alimentary digestion of food has also been observed. However, the distribution of these SCAAs in the gastrointestinal tract (GIT) has not been defined previously. This study aimed to examine the distributions of SCAAs and their corresponding short chain fatty acids (SCFAs) in the GIT of pigs. METHODS: Digesta samples were collected from the stomach, duodenum, jejunum, ileum, cecum, and rectum of 14 finishing barrows fed corn-soybean meal. The SCAAs and SCFAs in these samples were quantified by the liquid chromatography-mass spectrometry analysis, and their distribution in the GIT was further modeled by principal components analysis. RESULTS: SCAAs were far more abundant in the upper GIT than the lower GIT, with the highest concentrations of acetaldehyde and propanal in the stomach and the highest concentrations of butanal and pentanal in the duodenum and jejunum. In contrast, SCFAs were mainly present in the lower GIT, especially in the large intestine. CONCLUSIONS: The digestive activities in the upper GIT can produce significant amounts of SCAAs, which were mostly eliminated in the lower GIT. The converse distribution patterns of SCAAs and SCFAs in the GIT suggested that some SCAAs may be oxidized into SCFAs in the large intestine through microbial metabolism. FUNDING SOURCES: This study is partially supported by the AES project MIN-18-092.